Chapter 5 - Mathematical Proofs
Chapter 5 - Mathematical Proofs
Chapter 5 - Mathematical Proofs
Example:
(1) If x = 4, then 3 = 10 – 7. The conclusion is true regardless of the premise by trivial proof.
Vacuous Proof: If p is a conjunction of other hypotheses and we know one or more of these
hypotheses is false, then p is false and so p → q is vacuously true regardless of the truth value of q.
Example:
(2) If 4 is a prime number, then 32 = 6. The hypothesis “4 is a prime number” is false. Regardless of
whether the conclusion is true or false, the statement is vacuously true.
The first two methods of proof, the “Trivial Proof” and the “Vacuous Proof” are certainly the easiest
proofs you can use for as long as they work. Notice that the form of the “Trivial Proof”, q → (p → q),
is, in fact, a tautology. This follows from disjunction introduction, since p → q is equivalent to ¬p ∨ q.
Likewise, the “Vacuous Proof” is based on the tautology ¬p → (p → q).
Fill in the reasons for the following proof of the tautology ¬p → (p → q).
⇔ [(p ∨ ¬p) ∨ q]
⇔ True ∨ q
⇔ True
Exercises 5.1
1
Tell whether the statement is true or false. If true, give its proof.
1. Let xR, If x < 0, then x2+1 > 0.
2. Let xR. If x2 -2x+2 0, then x3 8.
3. If x > 0 then (x + 1)2 − 2x > x2.
4. If x is a prime number divisible by 16, then x2 < 0.
5. Let A = {1, 2, 3} and R = {(2, 3),(2, 1)}(⊆ A × A). If a, b, c ∈ A are such that (a, b) ∈ R and (b, c) ∈
R then (a, c) ∈ R.
We say the integer n is even if there is an integer k such that n = 2k. We say n is odd if there is an
integer k such that n = 2k + 1.
Example
Proof.
Assume n is an even number (n is a universally quantified variable which appears in the statement
we are trying to prove). Because n is even, n = 2k for some k (k is existentially quantified, defined
in terms of n, which appears previously). Now n2 = 4k2 = 2(2k2) (these algebraic manipulations are
examples of modus ponens). Let j=2k2 (j is existentially quantified, defined in terms of k); then n2
= 2j, so n is even (by definition).
Proof.
Assume m and n are odd numbers (introducing two universally quantified variables to stand
for the quantities mentioned in the statement). Because m and n are odd there are
integers j and k such that m = 2j + 1 and n = 2k + 1 (introducing existentially quantified
variables, defined in terms of quantities already mentioned). Now m + n = (2j + 1) + (2k + 1)
= 2(j + k + 1) (modus ponens). Let i = j +k+1 (existentially quantified); then m+n=2i is even
(by definition).
2
A common mistake of this type might arise as follows:
“Well, m is an odd integer, so I can write m = 2k + 1, where k is an integer.
Since n is also an odd integer, I can write n = 2k + 1, where k is an integer.”
Do you see the mistake? By allowing the same letter k to represent what might be different integers,
we have inadvertently added another assumption, namely, that m = n! Of course, we didn’t mean to
do this, but, unfortunately, our intentions haven’t been carried out, and so our proof breaks down at
this point. In order to maintain the “arbitrariness” of m and n, we must allow, at the least, that they
be different. We accomplish this by choosing different letters a and b in our representations of m and
n as “twice an integer plus one.” There is nothing sacred about a and b; we could have used k and j, or
x and y, or α and β, or any pair of symbols that have not been appropriated for some other use.
At times, the given proposition to be proven does not come in the form of an implication.
Example:
It’s not clear how to start a proof for a claim like this. What is our given information and what do
we need to show? In such cases, it is often useful to rephrase your claim using logical
equivalences. For example, the above claim is equivalent to
For every integer k, it is not the case that k is odd and k2 is even.
Since we’re assuming we all know that even and odd are opposites, this is the same as
And we can restate this as an implication using the fact that ¬p ∨ q is equivalent to p → q:
3
Our claim is now in a convenient form: a universal if/then statement whose hypothesis contains
positive (not negated) facts. And, in fact, we proved this claim last class.
Exercises 5.2
In the case that the sentence we are trying to prove is of the form P⇒Q, we assume that P is true
and Q is false (because P ∧ ¬Q is the negation of P⇒Q), and try to derive a statement known to be
false. Note that this statement need not be ¬P---this is the principal difference between proof by
contradiction and proof of the contrapositive. In a proof of the contrapositive, we assume that Qis
false and try to prove that P is false.
Example:
Proof:
a a
3 b b
Let = be positive integers a and b with no common factors (i.e., is in "lowest terms'').
a2
2
Then b = 3, so a2 = 3b2. Now 3 divides 3b2 and 3 divides a2. This implies that 3|a, so a = 3k for
4
some k. Then a2 = (3k)2 = 9k2 = 3b2, or 3k2 = b2. Now 3|b2, so 3|b. Thus we've shown that 3 divides both a
and b, but this contradicts the fact that a/b is in lowest terms. Hence, 3 cannot be written as a ratio
of whole numbers.
Proof:
Assume there are only finitely many primes p1,…,pk. Let n = p1⋯pk+1. Clearly n ≥ 2, so by the
corollary “Every integer n≥2 is divisible by some prime.” n is divisible by some prime, say pi.
Obviously, pi|(p1⋯pi⋯pk), so by theorem “If n|a and a|b, then n|b.”, pi|(n − p1⋯pk); Since n − p1⋯pk =
1, pi|1, a contradiction.
Exercises 5.3
A specific common sort of rephrasing is to replace a claim by its contrapositive. If the original
claim is p q, this can be transformed to its logically equivalent contrapositive form: q p.
The contrapositive consists of negations and swapping the hypothesis and conclusion. As such if
one wants to prove p q, he needs to rephrase this claim into the form q p.
Example:
(1) If you are to prove “For any integer k, if 3k + 1 is even, then k is odd.” using contrapositive,
what is its equivalent claim which you will use?
5
This is hard to prove in its original form, because we’re trying to use information about a derived
quantity to prove something about a more basic one. If we rephrase as the contrapositive, we get
Proof:
So, suppose that k is an integer and k is even. Then, k = 2m for some integer m. Then 3k + 1 =
3(2m + 1) = 6m + 3 = 2(3m + 1) + 1. Since m is an integer, so is 3m + 1. So 3k + 1 must be odd,
which is what we needed to show.
There is no hard-and-fast rule about when to switch to the contrapositive of a claim. If you are
stuck trying to write a direct proof, write out the contrapositive of the claim and see whether that
version seems easier to prove.
Exercises 5.4
1. For all integers m and n, if the product of m and n is even, then m is even or n is even.
2. For any integers a and b, a + b ≥ 15 implies that a ≥ 8 or b ≥ 8.
3. For every integer n, if n 2 is even, then n is even.
4. Let x ∈ Z. If x 2 − 6x + 5 is even, then x is odd.
At times, a proof would need to consider and exhaust all possible cases. The validity of this kind of
proof rests on the equivalence
This should not be confused with trying examples. The cases we consider are not specific
examples but still make use of arbitrary values. Moreover, an example even if using many of such
examples is not a proof.
6
Examples:
x2 4
(1) If x is a real number such that 0 , then either x > 2 or -2 < x < 1.
x 1
Proof:
x2 4
Let x be a real number for which the inequality 0 holds. Factor the numerator of the
x 1
( x 2)( x 2)
fraction to get the inequality 0 . For this combination of x + 2, x – 2 and x -1 to be
x 1
positive, either (1) all are positive or (2) two are negative and the other is positive. This gives four
cases to consider:
Case 1: x + 2 > 0, x – 2 > 0, and x – 1 > 0. This means x > -2, x > 2 and x > 1. The conjunct of all
these inequalities is x > 2.
Case 2: x + 2 > 0, x – 2 < 0, and x – 1 < 0. This implies x > -2, x < 2 and x < 1. The conjunct of all
these inequalities is -2 < x < 1.
Case 3: x + 2 < 0, x – 2 > 0, and x – 1 < 0. This implies x < -2, x > 2 and x < 1. The conjunct of all
these inequalities is { } or . Or simply, no such value x can satisfy all the required conditions.
Case 4. x + 2 < 0, x – 2 < 0, and x – 1 > 0. This implies x < -2, x < 2 and x > 1. The conjunct of all
these inequalities is { } or . Or simply, no such value x can satisfy all the required conditions.
(2) Prove that if n is a natural number less than 41, then n2 – n + 41 is a prime number.
Proof:
Recall that a prime number is an integer greater than 1 that is only divisible by itself and 1. It
would be nice if there was some general line of argument that would work, but, unfortunately,
there doesn’t seem to be an obvious one. As a result, the proof must be broken down into 41 cases
corresponding to n = 0, 1, 2, ..., 40. In each case we examine the integer n2 − n + 41 to see if it is
prime. For example, we can observe: n = 0: 02 − 0 + 41 = 41 is prime.
7
n = 0: 02 − 0 + 41 = 41 is prime.
n = 1: 12 − 1 + 41 = 41 is prime.
n = 2: 22 − 2 + 41 = 43 is prime.
n = 3: 32 − 3 + 41 = 47 is prime.
n = 4: 42 − 4 + 41 = 53 is prime.
As n increases, it becomes increasingly more time-consuming to show that n 2−n+41 is, indeed,
prime. For example, when n = 40, 402 − 40 + 41 = 1601. The simplest way to show that 1601 is
prime is to show that every prime number ≤ √ 1601 fails to be a divisor of 1601. There are 12 such
numbers to try, and you might as well check them on your calculator. Alternatively, you could
write a computer program or use a symbolic program such as Maple or Mathematica that has a
routine to test a number for primality.
Exercises 5.5
5.6 Biconditional
A biconditional statement is one where you are to prove “p if and only if q” or “p is equivalent to q”.
In order to establish the truth of the statement p ↔ q, use the fact that (p ↔ q) is equivalent to (p →
q) ∧ (q → p), and prove both implications using any of the previous methods.
A proof of a biconditional requires two proofs: the proof of an implication and a proof of its converse.
Our example below is very similar to theorems we have proved earlier. The point here is that the two
implications may be proved independently of each other, and the decision on the best strategy to use
should be made for each one separately.
8
Example:
Proof:
(a): We give a direct proof of this statement. Assume n is an odd integer. Then n = 2a + 1 for some
integer a. Then n2 = (2a + 1)2 = 4a2 + 4a + 1 = 2(2a2 + 2a) + 1, which is twice an integer plus 1.
Thus, n2 is odd.
(b): We give a proof of the contrapositive of this statement: “If n is even (not odd), then n2 is even
(not odd). Assume n is an even integer. Then n = 2a for some integer a. Then n2 = (2a)2 = 4a2 =
2(2a2), which is an even integer.
Exercises 5.6
Prove the following statements are equivalent.
5.7 Uniqueness
You are often asked to prove that some object satisfying a given property is unique. We’ve seen
before that the standard trick is to assume that there is another object satisfying the property, and
then show that it actually equals the original one.
Some of the most useful and interesting existence theorems are "existence and uniqueness
proofs''---they say that there is one and only one object with a specified property. The
symbol ∃!xP(x)stands for "there exists a unique x satisfying P(x),'' or "there is exactly one x such
that P(x),'' or any equivalent formulation.
Example:
9
(1) Let the universe of discourse be R. ∃!x(x2 + 1 = 2x): This is true since x = 1 is not only a
solution, but the only solution. (Can you prove it?)
(2) Let the universe of discourse be Z. ∀x∃!y(x < y < x + 2): This is true since only y = x + 1
satisfies the inequalities.
The quantifier ∃! can be broken down into the "existence'' part and the "uniqueness'' part. In
other words, ∃x!P(x) says the same thing as
The second part of this formula is the "uniqueness'' part; it says that any two elements that
satisfy P must, in fact, be the same. More often than not, we must prove existence and
uniqueness separately; quite frequently, the uniqueness part is the easier of the two.
(3) Let the universe of discourse be R. Prove that there is a unique function f(x) such that f′(x) =
2x and f(0) = 3.
Proof.
Existence: f(x) = x2 + 3 works.
Uniqueness: If f0(x) and f1(x) both satisfy these conditions, then f′0(x) = 2x = f′1(x), so they
differ by a constant, i.e., there is a C such that f0(x) = f1(x) + C. Hence, 3 = f0(0) = f1(0) + C =
3 + C. This gives C = 0 and so f0(x) = f1(x).
Exercises 5.7
A. Identify the existence part and the uniqueness part of your proof clearly.
1. There is a unique solution to 2x – 3 = 7.
2. For every x there is a unique y such that (x+1)3 – x3 = 3y + 1.
3. In the next two exercises, assume the universe of discourse is appropriate for a calculus
class.
4. There is a unique function f such that f′(x) = sin x, f(π/2) = 0.
5. There is a unique function f such that f′(x) = f(x) and f(0) = 1 (note f(x) = ex works. To
show uniqueness differentiate f(x) = e−x).
B. For the following values of a and b, find q and r such that 0 ≤ r < b and a = qb + r.
10
6. a = 81, b = 6
7. a = 728, b = 7
8. a = −11, b = 8
To do it in numbers:
11
Step 2 can often be tricky ... because we may need to use imaginative tricks to make it work!
Examples:
Prove that
(1) 3n - 1 is a multiple of 2.
Proof:
31 – 1 = 2 is a multiple of 2.
Is 3(k + 1) - 1 is a multiple of 2?
3(k + 1) – 1 = 3k 31 – 1
= 3k 3 – 1
= 2 3k + 1 3k – 1
= 2 3k + 3k – 1
Proof:
1 = 12 is true.
12
Step 2: Assume it is true for n = k:
k2 + (2k + 1) = k2 + 2k + 1,
Exercises 5.8
2. The rule of exponents is true for every natural number n: (ab)n = anbn.
3. The sum of n consecutive cubes is equal to the square of the sum of the first n numbers.
13
References
Copi, I. (1974). Symbolic logic. 4th ed. New York: Macmillan.
Klenk, V. (1994). Understanding symbolic logic. Englewood Cliffs, N.J.: Prentice Hall.
http://www.cs.odu.edu/~toida/nerzic/content/logic/pred_logic/quantification/quantification.html.
Retrieved April 9, 2015.
14